Political Discourse Analysis on Trump’s Ideology - Bayu Adi Sulistyo; Khristianto Khristianto (Lembaga Publikasi Ilmiah dan Penerbitan (LPIP), 2017)
This study belongs to Critical Discourse Analysis in sub-branch of Political Discourse. The analysis of this research uses the CDA theory by Norman Fairclough which is widely known as 3D model. Since CDA is closely related to ideology, this study investigates the ideology held by the text producer, speaker. The data used in this study is the speeches delivered by Trump in 2015 as the announcement of his decision to run in the US presidential race. Generally, there are two major topics in them: the dissatisfaction of the current government’s work, especially in economical and political aspect, and the negative perception on Islam. These are considered as Trump’s ideology. Based on the analysis, it can be inferred that Trump seems to have been successfull in creating his discourse. He has successfully persuaded the audience to be on his side. Keywords: CDA, political speech, 3D Model, U.S., Islam.